ГИМНАСТИКАЧИЛАРГА ТАЯНИБ САКРАШ МАШҚЛАРИНИ ЎРГАТИШ УСЛУБИЯТИ - Ешбаев, А.Ж.; Жарылкапов, У.Б. (SCIENCE and SOCIETY, 2024)
The article discusses the issues of teaching vaults taking into account the motor structure of movement, effective methods, means, the sequence of training and a weekly work plan is proposed.
Keywords: vault; training; weekly micro cycle; unsupported phase; landing; trajectory; technical training